3x-2 (y-1)=3×(-1)-2×(-4-1)=
3x-2y+2=-3+8+2
3x-2y=-3+8+2-2
3x-2y=5
597/12=x (ост. 9)
597-9=588
588/12=49
597/12=49 (ост. 9)
Ответ: 49.
Ответ:
Пошаговое объяснение:
Пусть данное число х. Тогда 24% его будут 0,24х. Составим уравнение
х+0,24х=22,4
1,24х=22,4
х=22,4:1,24
х=18 2/3
1дм 6см =16 см
16 - 9=7(см)
Ответ: кузнечик прыгнул расстояние длиной 7 см.
1) 3х+ху²-х²у-3у=(3х-3у)+(ху²-х²у)=3(х-у)+Ху(у-х)=(х-у)(3+Ху)
2)2а²-2b²-a+b=(2a²-2b²)-(a+b)=2(a²-b²)-(a-b)=2(a-b)(a+b)-(a-b)=(a-b)(2a+2b-1)
3)2x+y+y²-4x²=(2x-y)-(4x²+y²)=1(2x-y)-(4x²-y²)=1(2x-y)-(2x-y)(2x+y)=(2x-y)(1-2x+y)
4)a³-ab-a²b+a²=(a³+a²)-(ab-a²b)=a²(a+1)-ab(1+a)=(a+1)(a²-ab)
5)не знаю